Active and passive physicality: making the most of low fidelity physical interactive prototypes. (1st December 2014) - Hare, Joanna; Gill, Steve; Loudon, Gareth; Lewis, Alan
This paper presents three case-studies which comprise a systematic investigation into the use of low fidelity physical interactive prototyping techniques to form a design principle based on the constructs of active and passive physicality. It proposes that, with a better understanding of active and passive physicality, designers can make more effective prototypes for early stage user trials. Results of our studies indicate that the most effective prototypes balance both active and passive physicality equally. In addition, the notion of physicality can demonstrate why, in our studies; paper prototyping, screen-based prototypes and even Arduino prototypes produced unsatisfactory user data.